Changing paradigms in organ preservation and resuscitation. Issue 2 (April 2015) - Ali, Fadwa; Dua, Anahita; Cronin, David C.
<x xml:space="preserve">Abstract</x> Purpose of review Shortage of donor organs has increased consideration for use of historically excluded grafts. Ex-vivo machine perfusion is an emerging technology that holds the potential for organ resuscitation and reconditioning, potentially increasing the quality and number of organs available for transplantation. This article aims to review the recent advances in machine perfusion and organ preservation solutions. Recent findings Flow and pressure-based machine perfusion has shown improved kidney graft function and survival, especially among expanded criteria donors. Pressure-based machine perfusion is demonstrating promising results in preservation and resuscitation of liver, pancreas, heart, and also lung grafts. August 2014 marked Food and Drug Administration approval of XPSTM- XVIVO Perfusion System (XVIVO Perfusion Inc., Englewood, Colorado, USA), a device for preserving and resuscitating lung allografts initially considered unsuitable for transplantation. Although there is no consensus among physicians about the optimal preservation solution, adding antiapoptotic and cell protective agents to preservation solutions is an interesting research area that offers potential to improve preservation. Summary Ex-vivo machine perfusion of solid organs is a promising method that provides the opportunity for resuscitation and reconditioning of suboptimal grafts, expanding the number and quality of donor organs.